Revitalisasi Sabodam Sebagai Pengendali Aliran Lahar (Studi Kasus Di Daerah Gunungapi Merapi) - Cosmas Bambang Sukatja; Ardian Alfianto (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2017)
Mega-eruption of Merapi Volcano 2010 is a large-scale explosive eruption, destroying lava dome, removing cloud columns as high as 4 kilometers and bursts of in various directions at the volcano foot. Approximately 140 millions m3 of pyroclastic material spread through the 13 major rivers that source from Merapi. Lahar flow occurred in almost every river basin located beneath the active cone of Merapi. As a result of the lahar flow, as many as 77 of the 264 units of the sabo dam in the Merapi area were damaged or washed away by the lahar flows. The sabo dam controls the flow of lahar built up across the river channel to hold, accommodate and drain some of the material or sediment in order to carry the flow and pass water downstream. This study was conducted to find the cause of sabo dam damage, and the right solution after the eruption of Merapi 2010. The method used in qualitative descriptive approach. The results of this study were to revitalize sabo dam as lahar flow controller and as a reference in reviewing the master plan of a lahar flow control system in other volcanic areas.